2020
DOI: 10.3345/kjp.2019.00640
|View full text |Cite
|
Sign up to set email alerts
|

Asthma predictive index as a useful diagnostic tool in preschool children: a cross-sectional study in Korea

Abstract: Background: It is challenging to diagnose asthma in preschool children. The asthma predictive index (API) has been used to predict asthma and decide whether to initiate treatment in preschool children.Purpose: This study aimed to investigate the association between questionnaire-based current asthma with API, pulmonary function, airway hyperreactivity (AHR), fractional expiratory nitric oxide (FeNO), and atopic sensitization in preschool children.Methods: We performed a population-based cross-sectional study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 36 publications
(51 reference statements)
1
17
0
Order By: Relevance
“…In this study, the loose and stringent APIs had high negative predictive values (NPVs) of 98.7% and 98.6%, respectively but conversely had low positive predictive values (PPVs) of 12.7% and 14.1%. 8) The NPVs reported in this study were similar to those reported in the original study that showed the usefulness of the API; however, the PPVs in this study were lower. 9) In contrast, the API showed higher sensitivity and specificity in this study than in the original study; therefore, it can be considered applicable to patients with recurrent wheezing.…”
Section: Apisupporting
confidence: 86%
See 2 more Smart Citations
“…In this study, the loose and stringent APIs had high negative predictive values (NPVs) of 98.7% and 98.6%, respectively but conversely had low positive predictive values (PPVs) of 12.7% and 14.1%. 8) The NPVs reported in this study were similar to those reported in the original study that showed the usefulness of the API; however, the PPVs in this study were lower. 9) In contrast, the API showed higher sensitivity and specificity in this study than in the original study; therefore, it can be considered applicable to patients with recurrent wheezing.…”
Section: Apisupporting
confidence: 86%
“…Therefore, the study conducted by Lee et al 8) published in the current issue reveals the association between current asthma, the API and other tests.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The same group demonstrated that using natural language processing (NLP) mining of electronic health records for API criteria allowed for the ascertainment of asthma in children 9 ; the NLP-API predicted asthma with sensitivity 86%, specificity 98%, PPV 88%, and NPV 98% 9 . Similarly, a cross-sectional study in 916 Korean preschoolers showed that questionnaire-defined asthma was associated with stringent API+ (sensitivity 72.2%, specificity 82%, PPV 14.1%, NPV 98.6%, and 77% accuracy), but not with spirometry, airway hyperreactivity, exhaled nitric oxide, or atopic sensitization 6 . The authors speculated that the API may serve as a more reliable tool than those tests for the diagnosis of asthma in preschoolers; they also compared the API to other predictive models for asthma, and the API had higher LR+ and lower LR-6 .…”
Section: Discussionmentioning
confidence: 97%
“…The API has a compelling positive likelihood ratio (LR˜7.4 when applied by 3 years of age, for predicting a diagnosis of asthma by age 6), making it helpful in the identification of children at high risk for asthma; but its negative LR (˜0.75) is less helpful in ruling out the risk of incident asthma 4 . A recent cross-sectional study in preschoolers reported that the questionnaire-based diagnosis of asthma is associated with a positive API 6 . Our hypothesis is that the API could be used as a surrogate for asthma diagnosis in preschoolers from a longitudinal birth cohort.…”
Section: Introductionmentioning
confidence: 99%